Option C ,
40 degrees
Because angle Z was 70 (isosceles triangle)
Then 180-140=40 degrees
please answer also if you answer this one please answer my other one it basically the same
Answer:
D is the correct answer.
Step-by-step explanation:
Step 1: Write the data
Total number of songs = 100
Total ratio = 1
Total percentage = 100%
Ratio of jazz songs = 1/4
Percentage of jazz songs = 1/4 x 100 = 25%
Ratio of pop songs = 1 - 1/4 = 3/4
Percentage of pop songs = 3/4 x 100 = 75%
Step 2: Match the statement.
The correct statement is D; 25% are Julian's songs are jazz because 1/4 = 25/100 and 75% are pop because 3/4 = 75/100.
!!
Lexi and Maria had $250 altogether. After Lexi spent 2/5 of her money and Maria spent $40 they had the same amount of money left. How much more money did Lexi have in the beginning.
Answer:
The amount of money that Lexi had at the beginning was $131.25
Step-by-step explanation:
Let
x -----> amount of money that Lexi had at the beginning
y -----> amount of money that Maria had at the beginning
we know that
x+y=250 -----> equation A
(1-2/5)x=y-40
(3/5)x=y-40
y=(3/5)x+40 ----> equation B
substitute equation B in equation A and solve for x
x+(3/5)x+40=250
(8/5)x=250-40
(8/5)x=210
x=210*5/8
x=$131.25
Given the Arithmetic sequence A1,A2,A3,A4 45, 51, 57, 63 What is the value of A34?
Answer:
Value of A(34) = 219
Step-by-step explanation:
A1, A2,A3,A4,45,51,57,63 are in Arithmetic sequence
Common difference in this Arithmetic sequence = 63 - 57 = 06
so, A4 = 45 - 6 = 39
A3 = 39 - 6 = 33
A2 = 33 - 6 = 27
A1 = 27 - 6 = 21
First term of Arithmetic sequence = 21
Common difference = 06
Using general term of Arithmetic sequence,
A(n) = First term + (n - 1) common difference
A(34) = 21 + (34 - 1) 6
A(34) = 21 + 33 × 6
A(34) = 21 + 198
A(34) = 219
Value of A(34) = 219
which equation represents a line that passes through (0,-8) and (-5,23)
Answer:
[tex]\large\boxed{y=-\dfrac{31}{5}x-8}[/tex]
Step-by-step explanation:
The slope-intercept form of an equation of a line:
[tex]y=mx+b[/tex]
m - slope
b - y-intercept - (0, b)
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
====================================
We have the points (0, -8) → b = -8, and (-5, 23).
Substitute:
[tex]m=\dfrac{23-(-8)}{-5-0}=\dfrac{31}{-5}=-\dfrac{31}{5}[/tex]
Put the value of the slope and of the y-intercept to the equation of a line:
[tex]y=-\dfrac{31}{5}x-8[/tex]
The graph shows the relationship between the volume of a rectangular prism and the volume of a square pyramid with an identical bas and height what is the slope of the line
Answer:
what graph? there is no graph?
Which equivalent expression will be generated by applying the Distributive Property and combining like terms in the expression 11 + 4(x + 2y + 4)?
Answer:
27+4x+8y
or
4x+8y+27 ( I can reorder this a few different ways. I don't know what your choices are)
Step-by-step explanation:
11+4(x+2y+4)
We can apply distributive property to the 4(x+2y+4), this will give us 4x+8y+16.
Bring down the 11+ and we have 11+4x+8y+16.
The only like terms we have is 11 and 16. So reorder using commutative property and get 11+16+4x+8y.
I'm going to simplify the 11+16 part which gives us 27.
In the end we have 27+4x+8y.
Let me line up so it is all nice and neat:
11+4(x+2y+4)
11+4x+8y+16
11+16+4x+8y
27+4x+8y
Triangle XYZ is reflected across the y-axis. Then its image is rotated 90° about the origin. What are the
coordinates of the final image of point X under the composition of transformations?
• (-3,2)
• (3,2)
• (2-1)
0 (-2,-3)
None of the other answers are correct
Help me
Answer:
(- 3, 2 )
Step-by-step explanation:
Under a reflection in the y- axis
a point (x, y ) → (- x, y )
X has coordinates X(- 2, 3 ), hence
X'(2, 3 ) ← after reflection in the y- axis
Under a rotation about the origin of 90°
a point (x, y ) → (- y, x )
Hence
X'(2, 3 ) → X''(- 3, 2 ) ← final image point
The correct option will be option A: The final image point of X will be (-3,2).
What is reflection?The reflection about an axis is the transformation of the picture about an axis so that distance of every point from the axis before and after reflection will remain the same.
Here the coordinate of point X in triangle XYZ is (-2,3).
First, the triangle XYZ is reflected about the y-axis.
As we know, the reflection of the point of coordination (x,y) after reflection about the y-axis will be (-x,y).
(x,y)→(-x,y)
So the point X of coordination (-2,3) after reflection about the y-axis will be (2,3).
Then the reflected point is rotated about the origin.
As we know the rotation of the point of coordination (x,y) after rotation about origin will be (-y,x).
(x,y)→(-y,x)
So the point of coordination (2,3) after rotation about the origin will be (-3,2).
Therefore The final image point of X will be (-3,2).
Learn more about reflection
here: https://brainly.com/question/1908648
#SPJ2
which mapping diagrams represent functions (choose all that apply)
which mapping diagrams represent relations that are not functions (choose all that apply)
in mapping diagram D what is the domain
in mapping diagram D what is the range
Answer:
A) function
B) not function
C) not function
D) function
D has domain {1,3,5} and range {2,4,6}.
Step-by-step explanation:
So for a mapping diagram to show a function there can only be at most one line segment coming from a number in the first circle.
So let's look at the problems:
A) There is one segment coming from 2. (2 to 1)
There is one segment coming from 4. (4 to 3)
There is one segment coming from 6. (6 ro 5).
So this is a function.
The domain is the first numbers: {2,4,6}.
The range is the second numbers: {1,3,5}.
B) There is two segments coming from 1. So it is over with, this is not a function.
The domain is the first numbers: {0,1,4}.
The range is the second numbers: {-2,-1,0,1,2}.
C) There is two segments coming from a. So it is over with, this is not a function.
The domain is the first numbers: {a,b,c}.
The range is the second numbers: {4,5,6,7}.
D) There is one segment coming from each 1, 3, and 5. So this is a function.
The domain is the first numbers: {1,3,5}.
The range is the second numbers: {2,4,6}.
A rectangular flower bed is to be 8 m longer than it is wide. The flower bed will have an area of 84 m squared
What will it's dimensions be?
Answer:
6m wide
14m long
Step-by-step explanation:
Let the length be represented by L.
Let the width be represented by W.
We are given we want the length to be 8 m longer than it's width.
So we want L=8+W.
The area of the rectangle is 84 m squared, this means that LW=84.
So I'm going to substitute L=8+W into LW=84.
LW=84
(8+W)W=84 (L=8W)
So we are going to solve (8+W)W=84 for W.
(8+W)W=84
Distribute:
8W+W^2=84
Rearrange left hand side using commutative property:
W^2+8W=84
Subtract 84 on both sides:
W^2+8W-84=0
Now to factor a quadratic with leading coefficient 1 (assuming it isn't prime) is to find two numbers that multiply to be c=-84 and add up to be b=8.
I'm going to play with factor pairs that multiply to be -84
c=-84=4(-21)=12(-7)=6(-14)
So the number we are looking for is -6 and 14 since -6(14)=-84 and -6+14=8.
The factored form of our equation is:
(W+14)(W-6)=0
This means we need to solve both W+14=0 and W-6=0.
W+14=0
W=-14 (I subtracted 14 on both sides)
W-6=0
W=6 (I added 6 on both sides)
The solution W=-14 makes no sense.
W=6 is the solution for the width. That is the width is 6 m long.
Now the length is 8 more than the width so the length is 14 m long.
Answer:
6m wide and 14m long
Step-by-step explanation:
If a rectangular flower bed is to be 8 m longer than it is wide and the flower bed will have an area of 84 m squared, its dimensions will be 6m wide by 14m long.
L = length
W = Width
Solve for x in the equation x^2+ 4x-4=8.
X = -6 or x = 2
X=-2+or-2sqrt2
x = -2 or x = 6
x=2+or-2sqrt2
Answer:
x = -6 or x = 2
Step-by-step explanation:
The given equation is:
[tex]x^{2}+4x-4=8\\\\ x^2+4x-4-8=0\\\\ x^2+4x-12=0\\\\[/tex]
This is quadratic equation, so we can use the quadratic formula to find the roots of the equation i.e. the value of x that satisfy the given equation.
According to the quadratic formula, the two roots will be:
[tex]x=\frac{-b \pm \sqrt{b^{2}-4ac}}{2a}[/tex]
Here,
a = coefficient of x² = 1
b = coefficient of x = 4
c = constant term = -12
Using these values, we get:
[tex]x=\frac{-4 \pm \sqrt{(4)^2-4(1)(-12)}}{2(1)}\\\\ x=\frac{-4 \pm \sqrt{64}}{2}\\\\ x=\frac{-4 \pm 8}{2}\\\\ x = \frac{-4-8}{2} , x = \frac{-4+8}{2}\\\\ x=-6, x = 2[/tex]
Thus, the two values of x that satisfy the given equation are: -6 and 2. So 1st option gives the correct answer.
without actually performing the long division state whether 17 / 3125 will have a terminating decimal expansion or a non-terminating decimal expansion
Answer:
It is terminating decimal expansion.
Step-by-step explanation:
17/3125 is a terminating decimal expansion.
REASON:
If the factors of the denominator are in the form of 2^n 5^m then the rational number is a terminating decimal expansion otherwise it is recurring. Here n and m are non negative integers.
Proof:
Lets have a look on the solution of the given term.
17/1325
We will break the denominator in the factors:
If we multiply 5 five times than it will give us 1325.
17/1325 = 17/5^5 * 2^0 = 17/2^0 * 5^5
We know that any number with exponent zero = 1
∴ 2^0 = 1
So it satisfies our explanation that the factors of the denominator are in the form of 2^n * 5^m and n and m are non negative integers.
Thus this term has a terminating decimal expansion....
Answer:
Two of the most important characteristics of seawater are temperature and salinity – together they control its density, which is the major factor governing the vertical movement of ocean waters. The temperature of seawater is fixed at the sea surface by heat exchange with the atmosphere.
Step-by-step explanation:
plz mark as brainliest..
Simplify the following expression: square root of -36 + square root of -100 +7
Answer:
[tex]\large\boxed{\sqrt{-36}+\sqrt{-100}+7=7+16i}[/tex]
Step-by-step explanation:
[tex]\sqrt{-1}=i\\\sqrt{ab}=\sqrt{a}\cdot\sqrt{b}\\=====================\\\\\sqrt{-36}=\sqrt{(36)(-1)}=\sqrt{36}\cdot\sqrT{-1}=6i\\\sqrt{-100}=\sqrt{(100)(-1)}=\sqrt{100}\cdot\sqrt{-1}=10i\\\\\sqrt{-36}+\sqrt{-100}+7=6i+10i+7=7+16i[/tex]
Answer:
The answer is [tex]16i+7[/tex]
Step-by-step explanation:
In order to determine the answer, we have to know about imaginary numbers.
The imaginary numbers are different to real numbers because they use a new unit called "imaginary unit":
[tex]i=\sqrt{-1}[/tex]
i: imaginary unit
This new unit is applied like a factor when we have even roots with negative numbers inside.
In this case:
[tex]\sqrt{-36}=\sqrt{-1}*\sqrt{36}=6i\\\sqrt{-100}=\sqrt{-1}*\sqrt{100}=10i\\ \\\sqrt{-36}+\sqrt{-100}+7\\ 6i+10i+7\\16i+7[/tex]
Finally, the answer is [tex]16i+7[/tex]
(03.02)
If g(x) = 2(x - 4), find the value of x if g(x) = 20. (2 points)
Answer:
14
Step-by-step explanation:
20=2(x-4)
therefore, x=14
Answer:
2(x -4) = 20
2x - 8 = 20
2x = 28
x = 14
An elevator at a department store must carry fewer than 17 people at a time. An elevator operator is present in the elevator at all times. If x customers can travel in the elevator with the elevator operator, which inequality represents this situation? A. x + 1 < 17 B. x > 18 C. x + 1< 16 D. x < 17 E. x + 1 > 18
Answer:
A. x+ 1 < 17
Step-by-step explanation
Customers = x persons
Operator = 1 person
Total = x + 1 persons
Total persons must be less than 17.
The inequality is
x + 1 < 17
Solve the following addition and subtraction problems. 72km95hm+7g12cg18mg= 12dag5g−7g= 4kg2hg14kg+5kg17hg= 8kg−9g−−−−−−−−−−
Answer:
a. 8g 1dg 3cg 3mg
b. 11dag 8g
c. 24kg 9hg
d. 7kg 1hg
Step-by-step explanation:
Answer:
a. 8g 1dg 3cg 3mg
b. 11dag 8g
c. 24kg 9hg
d. 7kg 1hg
Step-by-step explanation:
got it from the other person
Quinton has an average resting heart rate of 70 beats per minute. When he runs, his heart rate increases by fewer than 50 beats per minute. If b represents his heart rate while running, which statements about the scenario are true? Check all that apply.
The inequality b=70<50 can be used to represent the situation.
The inequality b-50<70 can be used to represent the situation.
The graph of the solution set will be shaded to the left.
A possible value for b is 120.
A possible value for b is 140.
Answer:
1st and 3rd statements are true: 1) The inequality b=70<50 can be used to represent the situation and 2) The graph of the solution set will be shaded to the left.
Step-by-step explanation:
Lets look at this question step by step.
Quinton has an average resting heart rate of 70 beats per minute so heart rate = 70His heart rate increases by fewer than 50 beats per minute so heart rate = <50 or 70<50B represents heart rate while running, so 70 is the average resting heart and after running the heart rate is b = 70<50.Therefore, the first statement is true; The inequality b=70<50 can be used to represent the situation.
The inequality b-50<70 can be used to represent the situation.This cannot be true because as heart rate increases, it gets lesser than 50 so in this case, 50 is greater than 70 not lesser than 70.
Moreover, if we take 50 to the right side, it will be 70 + 50 = 120 which is wrong because b is supposed to be less than 50.
The graph of the solution set will be shaded to the left.This is true because b<50 and whenever there is a less than sign, the graph is shaded to the left.
A possible value for b is 120.A possible value for b is 140.These two statements cannot be true as be is supposed to be less than 50.
!!
Answer:
1 and 3
Step-by-step explanation:
pls give other person brainliest, they explained it very well:)
Which expression is equivalent sqrt10/4sqrt8
Answer:
The correct option is A
Step-by-step explanation:
The given expression is:
√10/4√8
We have to eliminate the √ from the denominator
4√8 = (2^3)^1/4
Multiply the whole expression by (2)^1/4
=(2)^1/4 * √10/ 2^(1/4)*(2^3)^(1/4)
= 2^(1/4) · 10^(2/4) / 2^1/4+3/4
=2^(1/4) · 10^(2/4) / 2^1+3/4
=2^(1/4) · 10^(2/4) / 2^4/4
=2^(1/4) · 10^(2/4) /2
=2^(1/4) · 100^(1/4) /2
=200^1/4 /2
= 4√200 /2
Thus the correct option is A....
Answer:
correct answer is a
Step-by-step explanation:
Which function represents the following graph?
00
Answer:
[tex]\large\boxed{y=\sqrt[3]{x+3}+3}[/tex]
Step-by-step explanation:
f(x) + n - shift the graph n units up
f(x) - n - shift the graph n units down
f(x + n) - shift the graph n units to the left
f(x - n) - shift the graph n units to the right
===========================================
The original graph ( y = ∛x) shifted 3 units to the left and 3 units up.
Therefore, the new equation is:
y = ∛(x + 3) + 3
WILL MARK BRAINLEST PLEASE HELP!!!!!
Answer:
C
Step-by-step explanation:
your answer will be option number
(3) {(1,1),(2,9),(4,8)}
I hopes its help's u
please follow me..!!
@Abhi.❤❤
if f(x) = x + 7 and g(x) = 1/x -13, what is the domain of (f O g)(x)
Answer:
domain of (f O g)(x) is {x|x≠0}
Step-by-step explanation:
Given:
f(x) = x + 7
g(x) = 1/x -13
Putting g(x) in f(x) i.e f(g(x))
(fog)(x)= 1/x -13 +7
= 1/x-6
Domain of 1/x-6 is {x|x≠0} !
For this case we have the following functions:
[tex]f (x) = x + 7\\g (x) = \frac {1} {x} -13[/tex]
We must find [tex](f_ {0} g) (x).[/tex] By definition we have to:
[tex](f_ {0} g) (x) = f (g (x))[/tex]
So:
[tex](f_ {0} g) (x) = \frac {1} {x} -13 + 7 = \frac {1} {x} -6[/tex]
By definition, the domain of a function is given by all the values for which the function is defined.
The function [tex](f_ {0} g) (x) = \frac {1} {x} -6[/tex] is no longer defined when x = 0.
Thus, the domain is given by all real numbers except zero.
Answer:
x nonzero
simplify the square root of 6 * the square root of 8
Answer:
4√3
Step-by-step explanation:
The question is to simplify √6 × √8
Applying surds
√6 can be written as √2 ×√3
and
√8 can be written as √2 × √4
but √4=2
so;
√8 is 2√2
Write the whole question as
√2×√3×2√2
This can be written as
2√2×√2×√3
But you know √2×√2 = √4 =2
So, write as
2×2×√3 = 4√3
4√3 is the simplified form
Simplified form of expression √6 × √8 is,
⇒ 4√3
We have to given that,
An expression to simplify,
⇒ √6 × √8
Simplify as,
⇒ √6 × √8
Since, √6 = √2 × √3
√8 = √2 × √2 × √2
Hence, We can write as,
⇒ √6 × √8
⇒ √2 × √3 × √2 × √2 × √2
⇒ 4√3
Therefore, Simplified form of expression √6 × √8 is,
⇒ 4√3
Learn more about the multiplication visit:
https://brainly.com/question/10873737
#SPJ6
Which normal distribution has the greatest standard deviation?
Answer with explanation:
Both the normal distribution curves have sample mean equal to 16.
Normal distribution curve 1 is more wider than Curve 2, resulting in greater standard deviation.
So, Curve 1 has the greatest standard deviation.
The first normal distribution curve has the greatest standard deviation.
Standard deviation describes how far from the mean the given data set spread out.
A normal distribution that is widely spread out has a high standard deviation while a normal distribution that is close to the mean has low standard deviation.From the given normal distribution curves, the first curve is widely distributed than the second which is clustered around the mean.Thus, we can conclude that the first normal distribution curve has the greatest standard deviation.
Learn more about normal distribution curve here: https://brainly.com/question/14644201
Help meeeeeeeeeeeeee
Answer: Second Option
[tex]f (x)=\frac{2}{x}[/tex] and [tex]g(x)=\frac{2}{x}[/tex]
Step-by-step explanation:
If we have a function f(x) and its inverse function [tex]f ^ {- 1} (x) = g (x)[/tex]
Then by definition:
[tex](fog) (x) = (gof) (x) = x[/tex]
Notice that the inverse of the function [tex]f (x)=\frac{2}{x}[/tex] is [tex]f ^ {- 1}(x)=\frac{2}{x}[/tex]
then:
If [tex]f (x)=\frac{2}{x}[/tex] and [tex]g(x)=\frac{2}{x}[/tex]
Then:
[tex](fog) (x) =\frac{2}{\frac{2}{x}}[/tex]
[tex](fog) (x) =\frac{2x}{2}[/tex]
[tex](fog) (x) =x[/tex]
The answer is the second option
please help , 1-10 , thanks !
Answers:
22
9
20
17
20
35
26
32
23
9
Solve -2 (t- 1) = 18
Answer:
t=-8
Step-by-step explanation:
-2 (t- 1) = 18
Divide each side by -2
-2 (t- 1)/-2 = 18/-2
t-1 = -9
Add 1 to each side
t-1+1 = -9+1
t = -8
Answer:
t = -8
Step-by-step explanation:
Isolate the variable, t. Note the equal sign, what you do to one side, you do to the other.
First, Divide -2 from both sides:
(-2(t - 1))/-2 = (18)/-2
t - 1 = 18/-2
t - 1 = -9
Isolate the variable t. Add 1 to both sides:
t - 1 (+1) = -9 (+1)
t = -9 + 1
t = -8
t = -8 is your answer.
~
Evaluate the function.
a. f(x) = 3x+5 {-2,0,2}
b. g(x) = x-9 find g(5)
c. f(n) = (3-n) + 4 {-1,-2,3}
Answer:
Part a) The values of the function f(x) are {-1,5,11}
Part b) The value of g(5) is -4
Part c) The values of the function f(n) are {8,9,4}
Step-by-step explanation:
Part a) we have
f(x)=3x+5
Evaluate for {-2,0,2}
1) For x=-2
substitute the value of x in the function
f(-2)=3(-2)+5=-1
2) For x=0
substitute the value of x in the function
f(0)=3(0)+5=5
3) For x=2
substitute the value of x in the function
f(2)=3(2)+5=11
Part b) we have
g(x)=x-9
Evaluate for x=5
substitute the value of x in the function
g(5)=5-9=-4
Part c) we have
f(n)=(3-n)+4
Evaluate for {-1,-2,3}
1) For n=-1
substitute the value of n in the function
f(-1)=(3-(-1))+4=8
2) For n=-2
substitute the value of n in the function
f(-2)=(3-(-2))+4=9
3) For n=3
substitute the value of n in the function
f(3)=(3-(3))+4=4
5xy-25x square+50x-10y
Answer:
the answer is 5(y-5x) (x-2)
Step-by-step explanation:
Answer:
[tex]5(x - 2)(y - 5x)[/tex]
Explanation
We want to factorize:
[tex]5xy - 25 {x}^{2} + 50x - 10y[/tex]
The factors have been grouped already. We now factor the GCF from each group to get:
[tex]5x(x- 5x) - 10(y - 5x)[/tex]
We factor further to obtain:
[tex](5x- 10)(y - 5x)[/tex]
We can still factor 5 to obtain:
[tex]5(x - 2)(y - 5x)[/tex]
Which point below is not on the graph of p(x) = +36- X?
(-13,7)
• (-35, 1)
O (11,5)
o (27,3)
SUBMIT ANSWER
ASK FOR HELD
Answer:
We have the following equation: y = 36 - x. And we need to find which of the following points belong to the graph:
(-13,7) (-35, 1) (11,5) (27,3)If any of the points belong to the equation, then the equality will be met.
Then:
(-13,7) :7 = 36 - (-13)
7 = 36 + 13
7 = 49 ❌
(-35, 1) :1 = 36 - (-35)
1 = 71❌
(11, 5) :5 = 36 - 11
5 = 25 ❌
(27,3)3 = 36 - 27
3 = 9 ❌
None of the points belong to the graph. Therefore, all points are NOT on the grah of p(x) = 36 - x.
Answer:
ANSWER IS (-35,1)
Step-by-step explanation:
I got it because I am looking at the answer right now
Zachary completes a hypothesis test and finds that he rejects the null hypothesis. Which statement gives a reason for rejecting
the null hypothesis?
The Z-statistic is less than 0.
The z-statistic lies in the critical region.
The Z-statistic lies outside the critical region.
The z-statistic is greater than 0.
Answer:
The z-statistic lies in the critical region
Step-by-step explanation:
When a hypothesis test is performed, the decision to reject or not reject the null hypothesis is made on basis of following observations:
If the z-statistic falls in the critical or rejection region, there is enough evidence to reject the Null HypothesisIf the z-statistic falls outside the critical or rejection region, there is not enough evidence to reject the Null Hypothesis.In the given statement Zachary rejects the Null Hypothesis, this means the z-statistic she calculated must have been inside the critical or rejection region. Hence the correct answer would be:
The z-statistic lies in the critical region
Answer: b) The z-statistic lies in the critical region.
ed21
Factor completely 3x² − x − 4.
20 for the top answer
Answer:
[tex](3x-4)(x+1)[/tex]
Step-by-step explanation:
This is in the form [tex]ax^2+bx+c[/tex].
If your wish is to factor by grouping, then you goal is too look for two numbers that multiply to be [tex]ac[/tex] and adds up to be [tex]b[/tex].
Then once you find those numbers you replace b with those numbers. Then the factor by grouping can be done.
So you have [tex]a=3,b=-1,c=-4[/tex]
[tex]ac=3(-4)[/tex]
[tex]b=-1[/tex]
The numbers that we need are already present since -4+3 is -1.
So replace -1 in
[tex]3x^2-1x-4[/tex]
with (-4+3)
[tex]3x^2-4x+3x-4[/tex]
Now group the first two terms together and group the last two terms together:
[tex](3x^2-4x)+(3x-4)[/tex]
Factor what you can from both pairs:
[tex]x(3x-4)+1(3x-4)[/tex]
Notice you have two terms: x(3x-4) and 1(3x-4). These terms have a common factor of (3x-4) so factor that out of our expression like so:
[tex](3x-4)(x+1)[/tex]
Check with foil if you like:
First: 3x(x)=3x^2
Outer: 3x(1)=3x
Inner: -4(x)=-4x
Last: -4(1)=-4
----------------------Add together:
3x^2-x-4
Answer: [tex]=(3x-4)(x+1)[/tex]
Step-by-step explanation:
Given the polynomial [tex]3x^2- x -4[/tex]
We can observe that it is written in this form:
[tex]ax^2+bx+c[/tex]
To factor completely, we need to follow these steps:
- Rewrite the term "b" as the sum of two terms whose product be [tex](3)(-4)=-12[/tex] and whose sum be -1:
[tex]=3x^2+(-4+3)x-4[/tex]
- Applying Distributive property, we get:
[tex]=3x^2-4x+3x-4[/tex]
- Make two groups of two terms each:
[tex]=(3x^2-4x)+(3x-4)[/tex]
- Factor out "x" from the first group and 1 from the second group:
[tex]=x(3x-4)+1(3x-4)[/tex]
- Factoring out [tex](3x-4)[/tex], we get:
[tex]=(3x-4)(x+1)[/tex]